5b+6-6b+r=19

Simple and best practice solution for 5b+6-6b+r=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b+6-6b+r=19 equation:


Simplifying
5b + 6 + -6b + r = 19

Reorder the terms:
6 + 5b + -6b + r = 19

Combine like terms: 5b + -6b = -1b
6 + -1b + r = 19

Solving
6 + -1b + r = 19

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -1b + -6 + r = 19 + -6

Reorder the terms:
6 + -6 + -1b + r = 19 + -6

Combine like terms: 6 + -6 = 0
0 + -1b + r = 19 + -6
-1b + r = 19 + -6

Combine like terms: 19 + -6 = 13
-1b + r = 13

Add '-1r' to each side of the equation.
-1b + r + -1r = 13 + -1r

Combine like terms: r + -1r = 0
-1b + 0 = 13 + -1r
-1b = 13 + -1r

Divide each side by '-1'.
b = -13 + r

Simplifying
b = -13 + r

See similar equations:

| 3j-8=5j+4 | | 5.4=3s | | x-69=-6x+99 | | -9=-6+3(5-m) | | 7(7x+5)=7(x-1) | | 5x-111=-7x+105 | | x=180-88 | | x+3.5=10.2 | | 2=3x-10 | | 4=14-k | | -2s-14s-5=11 | | -3t+7=-8t-3 | | 2d+d-3=6 | | p-7=-5 | | -4x+9(x-3)=10x+2 | | 20=8(v-90)-52 | | 3n+6=-10n-7 | | -10q-(-19q)-(-8)=17 | | 10-(-4)= | | 14n-13n=17 | | 3x(x-5)=2(x+4) | | 3=-(x+5) | | 4f=9+5f | | -16q+-4q=-20 | | 2(4x+5)=-14 | | 6x-3-6x=-33 | | 5(2p+1)=-4 | | -39+12x=7x+26 | | -2.75-18.4j=-3.88-18.5j | | -4j-4=-2j | | 6(7-f)+f=36+f | | f(x)=20x+10 |

Equations solver categories